Penerapan Model PBL Menggunakan Origami untuk Meningkatkan Kemampuan Pemecahan Masalah Kelas 2C SDN Kauman 1 Malang - Oktaviani, Mela; Restian, Arina; Kumalasari, Ratna (J-SES : Journal of Science, Education and Studies, 2025)
Mathematics at the elementary level is often faced with challenges in real-life problem-solving, including the understanding of plane shapes. The application of the Problem-Based Learning (PBL) approach can help students develop problem-solving skills more effectively. This classroom action research aimed to implement PBL using origami as a medium and evaluate its impact on problem-solving skills in class 2C of SDN Kauman 1 Malang, consisting of 27 students. The research was conducted in two cycles, each comprising several meetings. The results showed a significant improvement in students' problem-solving skills, with the average score increasing from the pre-cycle stage to the first cycle and then to the second cycle. The implementation of PBL with origami proved to help students understand plane shape concepts through an enjoyable and creative approach.